Juridical Analysis and Implementation of Ijarah Muntahiya Bit Tamlik (IMBT) Contracts in Sharia Banking: An Overview of the Elements, Anatomy of the Contract, and Legal Basis - Wahyu Eka Pratiwi, Sinthya; Sholihah, Silviatus (Jurnal Masharif Al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
The development of Islamic banking encourages innovative financing products that are in accordance with sharia principles, one of which is Ijarah Muntahiya Bit Tamlik (IMBT). This contract combines a leasing transaction with a promise of transfer of ownership at the end of the contract term. This study aims to analyze the juridical aspects, contractual elements, and anatomy of IMBT in Indonesian Islamic banking practices. This research uses normative legal research using legal and conceptual approaches. The results of the study show that IMBT has an adequate legal foundation both in sharia law and positive law; However, practical implementation still faces potential issues related to contract separation, WA'd clauses, and maintenance responsibilities. Therefore, stronger contract standardization and sharia compliance are needed to ensure IMBT practices remain consistent with prudential and sharia principles. Keywords: IMBT, ijarah, Islamic banking, contract, Islamic law